2011
DOI: 10.1007/s00417-011-1769-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological features and immunoreactivity of human choroidal and ciliary melanomas as prognostic factors for metastasis and death

Abstract: Our study suggests that conventional clinical and histopathological prognostic factors, and immunoexpression of β-catenin and LZTS1 combined may allow better prognostication of metastasis than clinical and histomorphological factors alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Basic characteristics of the presented pool of patients are comparable with those introduced in other published studies [16]. From among the clinical prognostic factors our results confirmed the negative prognostic value of the tumor size, "T" stage of the TNM classification and the mixed cytomorphological type of the neoplasm [17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…Basic characteristics of the presented pool of patients are comparable with those introduced in other published studies [16]. From among the clinical prognostic factors our results confirmed the negative prognostic value of the tumor size, "T" stage of the TNM classification and the mixed cytomorphological type of the neoplasm [17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…Kadkol et al [40] reported that the level of SPP1 expression was increased in the serum of patients with UM metastasis, and that tumors with looping high-risk vasculogenic mimicry patterns had increased expression of osteopontin. Another study [41] also looked at protein expression using a monoclonal antibody and did not observe a relation between expression and survival. In contrast to Kadkol and Simoes, we looked at mRNA and observed that decreased levels of SPP1 mRNA were associated with an unfavorable prognosis in UM.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the expression and copy number status of genes such as leucine zipper tumour suppressor 1 ( LZTS1 ), located on the 8p22 chromosomal band, has been considered in the evaluation of the prognosis of UM (Simoes et al. 2011; Wan et al. 2020); Onken et al., (2008a, 2008b) suggested that this gene acts as a metastatic regulator in UM.…”
Section: Introductionmentioning
confidence: 99%